A REVIEW STUDY OF THE ROLE OF VALUE CREATION CAPABILITIES AS A MECHANISM FOR ENHANCING SUSTAINABILITY IN BUSINESS - Hameedah Ghjaer Chraimukh (Scholars Digest Publishing, 2025)
This study proposes a theoretical model that helps researchers identify the relations between value creation capabilities and sustainability in business, as the key to the presentation of any innovative organization lies in the core values improved by sustainable resources, thus making value creation focus on doings that improve business performance as a mediating factor between outside and internal factors. It has become essential for organizations to redesign their business models to safeguard alignment between profitability on one hand and commitment to sustainability values on the other. The study focused on an analysis of the relevant works on the concept of value creation as a tool that contributes to finding new solutions to redefine the relationship between the organization and its stakeholders, and enhance its ability to continue in highly competitive work environments. The review of the literature also suggested that developing value creation strategies assists organizations in adopting environmentally and socially responsible practices, which contributes to balancing the economic goals and sustainable development requirements. However, improving sustainability is no longer a side activity but a strategic imperative that demands investment in new capabilities and institutional mechanisms that ensure the integration of sustainability into the fabric of organizational processes and activities
Keywords: Value Creation Capabilities, Sustainability, Exploration, Investment, Adaptation.